Analisis Kemampuan Berkomunikasi pada Anak Down Syndrome di SLB Negeri Selayar - Anwar, Afdaluddin; Nurhusna, Nurhusna; Fitri, Sakinah (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to describe the communication skills of children with Down syndrome at Selayar State Special Needs School (SLB Negeri Selayar). This study used a qualitative approach with data collection techniques through observation, interviews, and documentation. The subjects were children with Down syndrome identified as experiencing communication barriers. Data analysis techniques used in this study included data reduction, data presentation, and conclusion drawing. The results of this study indicate that children with Down syndrome at Selayar State Special Needs School (SLB Negeri Selayar) are better able to communicate nonverbally than verbally. The verbal communication skills of children with Down syndrome at Selayar State Special Needs School (SLB Negeri Selayar) are still relatively low. Children communicate more frequently nonverbally through touch, chronemics, body movements, and facial expressions. Among these nonverbal communication skills, there is still one form of communication that they have not yet mastered: chronemics, or the ability to manage time when speaking. Therefore, the results of this study are expected to serve as evaluation material and references in analyzing communication skills, particularly in children with Down syndrome.